2010
DOI: 10.3109/10673221003684000
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the Internet Safely: Recommendations for Residential Programs Targeting At-Risk Adolescents

Abstract: Adolescence is a period during human development characterized by a variety of biological, psychological, and social changes. Navigating these changes can be a stressful experience for both adolescents and their families. To complicate matters further, the Internet has altered the landscape of human interaction in a way that may accentuate deficits in the capacity for self-sustaining, reciprocal peer relationships. Adolescents suffering from emotional and behavioral disorders may be especially prone to this in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…As illustrated in the findings and recommendations, while increased degrees of adult support may be needed at times for individual situations or particularly vulnerable youth, supporting them to problem solve as they navigate online opportunities and confront harmful content is recognized as an effective approach. These skills include a combination of digital literacy skills, interpersonal skills, and emotion regulation strategies to address the technical, relational, and emotional elements of digital media use (Denby Brinson et al, 2015;Gustavsson & MacEachron, 2015;Pridgen, 2010). Gustavsson and MacEachron (2015) recommend addressing the heightened online risk among youth in out-of-home child welfare placements through a collaborative approach between youth and service providers.…”
Section: Treatment Implications: Integrating Treatment Goals and Digi...mentioning
confidence: 99%
See 1 more Smart Citation
“…As illustrated in the findings and recommendations, while increased degrees of adult support may be needed at times for individual situations or particularly vulnerable youth, supporting them to problem solve as they navigate online opportunities and confront harmful content is recognized as an effective approach. These skills include a combination of digital literacy skills, interpersonal skills, and emotion regulation strategies to address the technical, relational, and emotional elements of digital media use (Denby Brinson et al, 2015;Gustavsson & MacEachron, 2015;Pridgen, 2010). Gustavsson and MacEachron (2015) recommend addressing the heightened online risk among youth in out-of-home child welfare placements through a collaborative approach between youth and service providers.…”
Section: Treatment Implications: Integrating Treatment Goals and Digi...mentioning
confidence: 99%
“…While the degree of vulnerability among youth in RT varies in severity and complexity, they share characteristics that are associated with youth who are more affected by online harm (Anderson, 2017; Pridgen, 2010). Typically, between the ages of 13 and 18 years, youth in RT often have encountered adversity associated with traumatic experiences and/or characteristics increasing their vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…The available research on game addiction centers mostly on young males worldwide. There is some evidence to believe that the onset of IA is probably in late childhood/early adolescence [31]. There are many reports in countries such as China and South Korea.…”
Section: Epidemiology Of Internet Addictionmentioning
confidence: 99%
“…Adolescents who are lacking emotional and psychological support are found to be at highest risk and so are the adolescents with identified emotional and behavioral disorders [31].…”
Section: High-risk Groups For Internet Addictionmentioning
confidence: 99%
“…4 Reports suggest that the role of social media (e.g., cell phones and text messaging, social-networking sites, gaming sites, virtual worlds) in adolescent clinical presentations is increasingly common in child forensic practice 5 and among youth in residential care. 6 Researchers have therefore suggested that a significant part of the current generation's social and emotional development occurs relative to those technologies. 7 Empirical guidance on ways to manage such phenomena clinically is obviously needed.…”
mentioning
confidence: 99%